Net costs of class-size reduction: the portuguese case - Mucharreira, P.; Cabrito, B. G.; Capucha, L. (Cadernos de Pesquisa, 2019)
This article aims to promote further reflection on the benefits derived from class-size reduction, seeking to demonstrate that the expenditures resulting from this are usually overestimated when they are determined on the basis of gross employee cost to the State, and not taking into account the corresponding net costs. This scholarly exercise analyzes the Portuguese case and the costs of a teacher in the public education system in Portugal. This work intends to contribute to a better understanding of this subject, raising awareness of different educational actors of the relationship between cost and direct and indirect benefits of a class-size reduction policy.